Pengaruh Penerapan Teknik Expressive Writing dalam Mereduksi Perilaku Agresif Mahasiswa - Salmiati Salmiati; A. Aztri Fithrayani Alam; Nur Khaliza Usman (JURKAM: Jurnal Konseling Andi Matappa, 2021)
This type of research is a quasi-experiment which aims to determine the effect of the application of expressive writing techniques in reducing the aggressive behavior of STKIP Andi Matappa students. The population in this study are students who are indicated to have aggressive behavior based on the pretest results.  The population in this study were all students of STKIP Andi Matappa, totaling 215 students consisting of 3 study programs.  The samples of this study were 10 people from the guidance and counseling study program with the highest aggressive behavior in the class by applying expressive writing techniques to reduce aggressive behavior in students who were the research samples.  Data collection obtained through the results of the distribution of questionnaires The collection of data obtained through the provision of pretest questionnaires The analysis technique used is descriptive data analysis based on the results of Wilcoxon's hypothesis testing, the Asymp Sig value is 0.016, which means less than 0.05, this means H,  rejected and Hi accepted, namely the effect of applying expressive writing techniques to reduce the aggressive behavior of students at STKIP Andi Matappa Artinva, expressive writing techniques can be used as one of the tools to reduce aggressive behavior towards students at STKIP Andi Matappa